Postoperative early ambulation in neurosurgical patients: influencing factors and nursing strategies - Xu, Yan; Yin, Xiangyi; Xia, Yi; Qian, Xing (Frontiers in Neurology, 2025)
BackgroundEarly postoperative ambulation holds significant implications for patient prognosis. The present study aims to analyze the implementation rate of early postoperative ambulation in neurosurgical patients, identify its independent influencing factors, and provide evidence-based support for optimizing clinical treatment and nursing interventions.MethodsThe study population comprised neurosurgical patients admitted to a tertiary medical center in Jiangsu Province, China, between January 2024 and May 2025. Comprehensive perioperative data—encompassing baseline demographics and early postoperative ambulation status—were analyzed to identify influencing factors of early postoperative ambulation.ResultsA total of 268 neurosurgical patients were included, among whom 85 (31.7%) achieved early postoperative ambulation. Correlation analyses demonstrated that age (r = −0.586), body mass index (BMI; r = −0.520), presence of a postoperative drainage catheter (r = −0.590), duration of surgery (r = −0.587), and postoperative Visual Analog Scale (VAS) score (r = −0.614) all exhibited significant inverse associations with early postoperative ambulation. Logistic regression analysis identified five independent factors influencing early postoperative ambulation: age ≥ 60 years (odds ratio [OR] = 2.859, 95% confidence interval [95%CI]: 1.532–3.654), BMI ≥ 24 (OR = 2.194, 95%CI: 1.126–3.047), presence of a postoperative drainage catheter (OR = 2.706, 95%CI: 1.830–3.625), surgical duration ≥ 120 min (OR = 1.973, 95%CI: 1.285–2.585), and postoperative VAS score ≥ 3 (OR = 3.142, 95%CI: 2.869–3.704).ConclusionThe rate of early postoperative ambulation completion among neurosurgical patients is relatively low, with multiple factors influencing this outcome. Targeted nursing interventions are warranted to improve the implementation of postoperative ambulation in neurosurgical patients.